If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25x + -2 = 40 + 4 Reorder the terms: -2 + 25x = 40 + 4 Combine like terms: 40 + 4 = 44 -2 + 25x = 44 Solving -2 + 25x = 44 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 25x = 44 + 2 Combine like terms: -2 + 2 = 0 0 + 25x = 44 + 2 25x = 44 + 2 Combine like terms: 44 + 2 = 46 25x = 46 Divide each side by '25'. x = 1.84 Simplifying x = 1.84
| 2x(2x-4)=0 | | 4.72f-0.5=-61.6f-8 | | 2.1k=9.66 | | ((2x-7)/x)=((x-2)/5) | | 7-3/4c=65 | | -8x+9x-13x= | | 4-3x=8(1-x) | | -7-3=9x+5-8x | | .3(y+8)+8=.16(9y-24)-4 | | 7(x-2)+3x=6x+18 | | t/12=3 | | -10+22=m-6 | | y=5+12 | | 5y+2+4y=112 | | -(5x-7)-(4x-4)+8=-8(x-3)-(8x+9)+8 | | 2l-3y=36-6y | | 3k-4/2=5 | | 3b-5=2b+1 | | 16x+15=4x-9 | | 6y+1=61 | | -3x/4+1=7/12 | | 3x-3y=27 | | 3y+2y+y= | | x^2+xy+y^2=7 | | 8(1+w)=7(8+w) | | 5z-1=z+7 | | 7(x-3)-(6-2x)=-3x-2(5-x) | | 7x-11-4x=5x-8 | | 2msquared+1=19 | | (x+2)(x-2)=35 | | -4a+6+5a=15-22 | | 3x+2-3=8 |